Importance of Technology-based Entrepreneurship in the Education - W Wardana; N Heriyati; Dina Oktafiani; Theresia Valentina Lumban Gaol (President University, 2022)
This research aims to discuss the importance of using technology-based entrepreneurship in education. This research used documentation method to gather data about various things or variables in written form. This research indicated that proper technology management in entrepreneurship education can improve business and increase the ratio of entrepreneurs by 2% of the total population in Indonesia. Technopreneurship can be learned through the world of education as a transformation, namely the development of entrepreneurship studies by utilizing information technology as a basis.